2021
DOI: 10.1111/ene.15162
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone‐derived keystroke dynamics are sensitive to relevant changes in multiple sclerosis

Abstract: Background To investigate smartphone keystroke dynamics (KD), derived from regular typing, on sensitivity to relevant change in disease activity, fatigue, and clinical disability in multiple sclerosis (MS). Methods Preplanned interim analysis of a cohort study with 102 MS patients assessed at baseline and 3‐month follow‐up for gadolinium‐enhancing lesions on magnetic resonance imaging, relapses, fatigue and clinical disability outcomes. Keyboard interactions were unobtrusively collected during typing using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Despite this, the use of KD in the assessment of diseases is relatively underutilized, especially considering that touchscreen typing has existed for over a decade. Hence, our objective was to validate the use of passive KD, measured with the Neurokeys app, to improve disease management in MS. To this end, earlier investigations by our research group reported on the clinimetric properties of reliability, validity, and 3-month responsiveness of KD in MS [ 10 , 11 ]. To the best of our knowledge, other applications of KD analysis in diseases are limited to the detection of early-stage Parkinson disease [ 23 - 28 ], upper limb dysfunction in amyotrophic lateral sclerosis [ 29 ], and severity in mood disorders [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, the use of KD in the assessment of diseases is relatively underutilized, especially considering that touchscreen typing has existed for over a decade. Hence, our objective was to validate the use of passive KD, measured with the Neurokeys app, to improve disease management in MS. To this end, earlier investigations by our research group reported on the clinimetric properties of reliability, validity, and 3-month responsiveness of KD in MS [ 10 , 11 ]. To the best of our knowledge, other applications of KD analysis in diseases are limited to the detection of early-stage Parkinson disease [ 23 - 28 ], upper limb dysfunction in amyotrophic lateral sclerosis [ 29 ], and severity in mood disorders [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a prospective cohort study at the MS Center of the Amsterdam University Medical Centers (VU University Medical Center location). The study design and interim analyses have been reported previously [ 10 , 11 ]. In brief, after a baseline assessment (M 0 ), we followed the patients for 1 year, with clinical visits every 3 months (M 3 , M 6 , M 9 , and M 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 In MS, keystroke dynamics have been linked with performances on motor and cognitive tests, brain lesions, and neurological disability. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…Existing keystroke studies in MS have only used a brief cognitive screener measuring processing speed. 14 , 15 Studies in populations with cognitive impairment as a primary feature (e.g., mild cognitive impairment and dementia) focus on classification between clinical and control groups 16 , 17 ; thus, associations between keystroke features and specific cognitive domains remain unknown. The goal of the current study was to provide proof-of-concept evidence that keystroke dynamics have the potential to be used as an unobtrusive remote monitoring method for real-life cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%